Prison, Architecture and Humans - Johnsen, Berit; Giofrè, Francesca; Fransson, Elisabeth (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"What is prison architecture and how can it be studied? How are concepts such as humanism, dignity and solidarity translated into prison architecture? What kind of ideologies and ideas are expressed in various prison buildings from different eras and locations? What is the outside and the inside of a prison, and what is the significance of movement within the prison space? What does a lunch table have to do with prison architecture? How do prisoners experience materiality in serving a prison sentence? These questions are central to the texts presented in this anthology. Prison, Architecture and Humans is the result of a collaboration between researchers and architects from Italy, Norway and Sweden. It presents new approaches to prison architecture and penological research by focusing on prison design, prison artefacts, everyday prison life and imprisoned bodies. The book will be of interest to students, researchers, architects and politicians."